Effect of cereal fibre source and processing on rectal epithelial cell proliferation. Issue 2 (1st August 1997) - Macrae, F A; Kilias, D; Selbie, L; Abbott, M; Sharpe, K; Young, G P
Abstract : Background —Low fat and wheat bran interventions significantly reduced the growth of small to large adenomas and modestly suppressed rectal epithelial cell proliferation in the Australian Polyp Prevention Project. Aim —To study the effect of unprocessed wheat bran, unprocessed oat bran and processed wheat bran (Kellogg's All Bran) on rectal epithelial cell proliferation. Patients —Twenty subjects with recent adenomas and a high fat background diet were recruited. Methods —Rectal biopsy specimens were taken at entry and at the end of three six-week periods of oat bran (64 g/day), wheat bran (25 g/day) and All Bran (38 g/day), all in association with a diet <25% energy as fat, in a randomised cross-over trial. Each of the bran supplements had a total of 11 g dietary fibre. The biopsy specimens were fixed in methacarn and stained immunohistochemically for presence of the proliferating cell nuclear antigen (PCNA). The kinetics used to measure proliferation were labelling index, whole distribution of labelled cells, and labelled cells in the top two-fifths of crypts using analysis of variance. Results —There were no significant differences in mean labelling indexes between the four diets or in the percentage of labelled cells in the top two-fifths (p=0.59), but activity in the top two-fifths of crypts was lowest with wheat bran. The mean (SD) labelling indexes were 2.23 (0.11)% for control, 2.13 (0.08)% for wheat bran, 2.19 (0.09)% for oat bran, and 2.12 (0.08)% for All Bran. The proportion in the top two-fifths of the crypts was 2.6 (0.6)% for control, 2.15 (0.5)% for wheat bran, 3.3 (0.9)% for oat bran, and 3.1 (0.9)% for All Bran. On analysis of whole distribution, there was no significant overall effect of diets but there was a difference between subjects. Analysis including total fibre intake also did not identify effects on proliferation. Conclusion —In this study of high risk subjects with initial high fat diets, dietary fibre in association with a low fat diet had no effect on rectal epithelial cell proliferation, although wheat bran had the greatest effect on percentage of labelled cells in the top two-fifths of crypts.